1995
DOI: 10.1002/cyto.990190103
|View full text |Cite
|
Sign up to set email alerts
|

Hardware and software requirements for quantitative analysis of comparative genomic hybridization

Abstract: Key terms: Background correction, CCD camera., filters, fluorochromes, image quality assessment. intensity normalization, pixel shift correction, relative copy number karyotypeComparative Genomic Hybridization (CGH) analysis (4) has rapidly established itself as a powerful method for analyzing whole genomic DNA (3, 5 , 6, 10, 14, 15), and many researchers are interested in acquiring their own CGH analysis capability. Although some chromosomal imbalances, e.g. high copy number amplifications, can be identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 12 publications
0
45
0
Order By: Relevance
“…For CGH analysis, image acquisition and processing were performed using the Cytovision System (Applied Imaging), version 3.1. The diagnostic threshold values used to score losses and gains were 0.75 (lower threshold) and 1.25 (upper threshold), respectively, in accordance with previously reported CGH analysis protocols (Du Manoir et al, 1995).…”
Section: Mutation Analysis Of Tp53 Microsatellite Analysis and Compmentioning
confidence: 74%
“…For CGH analysis, image acquisition and processing were performed using the Cytovision System (Applied Imaging), version 3.1. The diagnostic threshold values used to score losses and gains were 0.75 (lower threshold) and 1.25 (upper threshold), respectively, in accordance with previously reported CGH analysis protocols (Du Manoir et al, 1995).…”
Section: Mutation Analysis Of Tp53 Microsatellite Analysis and Compmentioning
confidence: 74%
“…The central line in the pro®les represents the most frequently measured¯uorescence ratio for each metaphase spread, corresponding to a balanced state of chromosomal material. The right and left vertical lines de®ne threshold values for over-and underrepresentation of chromosomal material (du Manoir et al, 1995).…”
Section: Genetic Analysis By Comparative Genomic Hybridization (Cgh)mentioning
confidence: 99%
“…Whereas a normal karyotype was obtained with some of the reference DNAs, others, in particular reference DNA A, led to numerous deviations in the same samples. Inconsistent results due to different reference DNAs were also reported for chromosome 19 by duManoir et al [15], who found that the deviations disappeared after changing the reference DNA. The authors explained their observation by varying contents of short interspersed repetitive elements, leading to low suppression in the hybridization procedure.…”
Section: Discussionmentioning
confidence: 67%